Diseminasi Hukum Humaniter Internasional Dalam Upaya Menyebarkan Semangat Perdamaian - Gunawan, Yordan; Pratama, Naufal Bagus (Turast: Jurnal Penelitian dan Pengabdian, 2020)
Dissemination of International Humanitarian Law to Promote Spirit of Peace. International Humanitarian Law (IHL) is one of a very important branch of International Law that need to be disseminate not only to Red Cross, Military, or Police Personnel, but also to the public as a whole, especially the youth. The need of this dissemination program is to limit the casualties from an armed conflict, to guarantee and secure the victims of war, encouraging participation on humanity, and spread the spirit of peace. This community service program is an obligation for all countries that are party to the Geneva Convention 1949, yet the country alone will face difficulty to reach all the elements of the society. Therefore, there is a need of community service program to disseminate IHL. This program aims the senior high school students in Yogyakarta. The dissemination will be conducted in forms of seminar delivered by the speaker which is a lecturer and a researcher in Universitas Muhammadiyah Yogyakarta, group discussion and role playing in a form of TFG (tactical Floor Gaming). After participating in this program, the participants are expected to understand and uphold the IHL and protection to Red Cross and Red Crescent emblem, and able to implement the gained knowledge, especially in conflict resolution, upholding peace, and actively participate in humanity activity.Keywords: International Humanitarian Law, Dissemination, Geneva Convention 1949